From Family Literacy to Literacies in the Context of Newcomer Family Relationships: Mapping Literacies with Home Visitors from Home Instruction for the Parents of Preschool Youngsters (HIPPY) - Bastien, Maria (Université d'Ottawa / University of Ottawa, 2017)
This qualitative research project reconceptualizes conventional and prescriptive views of family literacy as literacies in the context of family relationships, experimenting with data from the home visitor participants of one international family literacy intervention program (FLIP): Home Instruction for the Parents of Preschool Youngsters (HIPPY). Participants of the HIPPY program in Canada primarily include newcomer families. While the program targets conventional forms of literacy and education relating to children’s school readiness, in practice their work with these families goes far beyond this initial focus further engaging with issues related to settlement. For example, after completing HIPPY’s two-year program successfully with their own children, parents can be hired to become home visitors, receive professional development and guide newcomer families through the HIPPY materials they will use with their children. Using the theoretical and practical lens of Multiple Literacy Theory (Masny, 2006, 2009, 2013) this project asks what literacy practices home visitors engage in with newcomer parents, how these practices function in the relationship, and what these practices produce in these interactions. Lombard (1981) recognized the need for further research on home visitor experiences after program coordinators noted the “highly visible changes in home visitors’ level of understanding and performance” (p. 89). Since then, however, parents and children continued to be the main focus of research. This project seeks to to illuminate the under-researched experiences of HIPPY home visitors. Using the theoretical and practical lens of Multiple Literacy Theory (Masny, 2006, 2009, 2013) and the philosophy of Deleuze and Guattari (1987), qualitative observation and interview data were collected and analyzed through the process of rhizoanalysis, creating four mappings. The first mapping experiments with HIPPY not as an isolated program, but as part of a much larger assemblage of programs and services focused on newcomers in a Canadian community. The second mapping looks closely at HIPPY and English language acquisition. Mapping three experiments with conceptualizations of HIPPY home visitors as instructors of “Canadian culture”, and the fourth and final mapping delves into a more specific cultural focus on home and school connections. The final chapter of the dissertation is not a conclusion, but a look forward. This chapter introduces the concept of literacies in the context of family relationships as an integral part of not only early learning, but public and community health.
Keywords: family literacy; family literacy intervention programs; literacies; immigration; newcomers; assemblage; rhizome; Home Instruction for the Parents of Preschool Youngsters (HIPPY)